1990
DOI: 10.2307/3430949
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Potential Risk to Workers from Exposure to 1,3-Butadiene

Abstract: The available epidemiologic data provide equivocal evidence that 1,3-butadiene is carcinogenic in humans; some available studies suggest that the lymphopoietic system is a target, but there are inconsistencies among studies in the types of tumors associated with 1,3-butadiene exposure, and there is no evidence of a relationship between length of exposure and cancer risk, as one might expect if there was a true causal relationship between 1,3-butadiene exposure and cancer risk. The available chronic animal stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

1990
1990
2001
2001

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 20 publications
0
13
0
2
Order By: Relevance
“…The modeled exposure concentrations appears to be consistent with monitored off-site concentrations. Modeled estimates of fenceline concentrations and occupational monitoring of fenceline concentrations are also similar (30,31).…”
Section: Exposure Assessmentmentioning
confidence: 77%
“…The modeled exposure concentrations appears to be consistent with monitored off-site concentrations. Modeled estimates of fenceline concentrations and occupational monitoring of fenceline concentrations are also similar (30,31).…”
Section: Exposure Assessmentmentioning
confidence: 77%
“…For example, Turnbull et al (14) found only limited consistency when they compared animal results to the largest of three cohorts with exposure to 1,3-butadiene. The chosen study, (16) however, was the only one of the three that did not report an overall excess of lymphatic or hematopoietic cancer.…”
Section: Choice Of Human Studymentioning
confidence: 96%
“…(14) In these instances, the exposure of concern has generally caused cancer at more than one site in rodents. We believe that the rationale for such a comparison is weak, because a single chemical exposure only occasionally produces excess tumors at multiple sites in people and rarely or never at all sites.…”
Section: Tumor Typementioning
confidence: 99%
See 1 more Smart Citation
“…For that reason risk estimation from animal tests should be based on the doses of essential metabolites measured in both animal models and humans. For these reasons criticism of risk estimation of butadiene from experimental data is well-founded, particularly since comparison with epidemiological data indicate that such extrapolation leads to erroneous values (106).…”
Section: Alkenes Ethenementioning
confidence: 99%